High-voltage direct current (HVDC) systems. Guidance to the specification and design evaluation of AC filters. AC side harmonics and appropriate harmonic limits for HVDC systems with voltage sourced converters (VSC) Part 5, (29th September 2021) - British Standards Institution,
No abstract available